2007
DOI: 10.1111/j.1462-2920.2007.01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of highly host‐specific cyanophages in the estuarine environment

Abstract: Cyanophages that infect coastal and oceanic Synechococcus have been studied extensively. However, no cyanophages infecting estuarine Synechococcus have been reported. In this study, seven cyanophages (three podoviruses, three siphoviruses and one myovirus) isolated from four estuarine Synechococcus strains were characterized in terms of their morphology, host range, growth and genetic features. All the podoviruses and siphoviruses were highly host specific. For the first time, the photosynthesis gene (psbA) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
145
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(159 citation statements)
references
References 60 publications
13
145
1
Order By: Relevance
“…P60 is a lytic phage that infects Synchococcus WH7805 (Chen and Lu, 2002), a cyanobacterium isolated from the Atlantic Ocean (Waterbury et al, 1986). P60 was recognized as a highly active phage because of its short latent period compared to other cyanophages (Wang and Chen, 2008). All the oceanic sequences in this subcluster shared greater than 97% amino-acid identity with P60, suggesting that P60-like podoviruses are common in the ocean and could be critical in regulating the population dynamics of oceanic cyanobacteria.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…P60 is a lytic phage that infects Synchococcus WH7805 (Chen and Lu, 2002), a cyanobacterium isolated from the Atlantic Ocean (Waterbury et al, 1986). P60 was recognized as a highly active phage because of its short latent period compared to other cyanophages (Wang and Chen, 2008). All the oceanic sequences in this subcluster shared greater than 97% amino-acid identity with P60, suggesting that P60-like podoviruses are common in the ocean and could be critical in regulating the population dynamics of oceanic cyanobacteria.…”
Section: Resultsmentioning
confidence: 90%
“…A recent study showed that podoviruses infecting marine picocyanobacteria contain a conserved DNA polymerase gene (DNA pol), which can be used as a gene marker to investigate the genetic diversity of these viruses (Wang and Chen, 2008). PCR amplification, cloning and sequencing of this viral DNA pol gene from field samples have uncovered new genotypes and subclusters of cyanopodoviruses in the Chesapeake Bay (Chen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon biomass was calculated according to Verity et al (1992 Amplification of psbA genes PsbA gene fragments (B750 bp) were amplified by PCR from cDNA and genomic DNA using the degenerated PCR primers designed by Wang and Chen (2008) that target the conserved YPIWEA and HNFPLD regions. PCR was performed in a total volume of 25 ml containing 10 ng of template DNA/cDNA, 2.5 ml of 10 X OptiBuffer, 2 ml of dNTP, 1.3 ml of 50 mM MgCl 2 , 1 ml of 25 mM psbA-1F (TAYCCNATYTGGGAAGC), 1 ml of 25 mM psbA-2R (TCRAGDGGGAARTTRTG), and 1.2 U of BIO-X-ACT (Bioline, London, UK).…”
Section: Carbon Biomass Estimationsmentioning
confidence: 99%